2018
DOI: 10.5194/angeo-2018-20
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetosheath jet properties and evolution as determined by a global hybrid-Vlasov simulation

Abstract: Abstract. We use a global hybrid-Vlasov simulation for the magnetosphere, Vlasiator, to investigate magnetosheath highspeed jets. Unlike many other hybrid-kinetic simulations, Vlasiator includes an unscaled geomagnetic dipole, indicating that the simulation spatial and temporal dimensions can be given without scaling. Thus, for the first time, this allows investigating the magnetosheath jet properties and comparing them directly with the observed jets within the Earth's magnetosheath. In the run shown in this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…However, the large extent of the magnetosheath in the simulation does not affect the local physics that occur at the bow shock, in the magnetosheath, and at the magnetopause. Vlasiator simulations have been found to reproduce observed features of the foreshock velocity distributions and waves (Kempf et al, ; Palmroth et al, ; Pfau‐Kempf et al, ; Turc et al, ), foreshock transients (Blanco‐Cano et al, ), magnetosheath mirror mode waves (Hoilijoki et al, ) and high‐speed jets (Palmroth et al, ), and reconnection rates at the dayside magnetopause (Hoilijoki et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the large extent of the magnetosheath in the simulation does not affect the local physics that occur at the bow shock, in the magnetosheath, and at the magnetopause. Vlasiator simulations have been found to reproduce observed features of the foreshock velocity distributions and waves (Kempf et al, ; Palmroth et al, ; Pfau‐Kempf et al, ; Turc et al, ), foreshock transients (Blanco‐Cano et al, ), magnetosheath mirror mode waves (Hoilijoki et al, ) and high‐speed jets (Palmroth et al, ), and reconnection rates at the dayside magnetopause (Hoilijoki et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding jets, it has been suggested that jets associated with SLAMS can have a relative increase of density and magnetic field strength whereas the ones associated with purely bow shock ripple mechanism may be mainly velocity driven (Karlsson et al, 2015). Furthermore, there have been recent simulations supporting the creation of a SLAMS-like subset of jets (Palmroth et al, 2018).…”
Section: Generation Of Jetsmentioning
confidence: 99%
“…Regarding jets, it has been suggested that jets associated with SLAMS can have a relative increase of density and magnetic field strength whereas the ones associated with purely bow shock ripple mechanism may be mainly velocity driven (Karlsson et al, 2015). Furthermore, there have been recent simulations supporting the generation of a SLAMS‐like subset of jets (Palmroth et al, 2018).…”
Section: Introductionmentioning
confidence: 99%